Cycles of violence and terrorist attacks index for the State of Arizona - Gómez-Sorzano, Gustavo
I apply the Beveridge-Nelson business cycle decomposition method to the time series of per capita murder in the State of Arizona (1933-2005). Separating out “permanent” from “cyclical” murder, I hypothesize that the cyclical part coincides with documented waves of organized crime, internal tensions, breakdowns in social order, crime legislation, social, and political unrest, and recently with the periodic terrorist attacks to the U.S. The estimated cyclical component of murder warns that terrorist attacks in the U.S. soil, and foreign wars fought by the country from 1941 to 2005, have affected Arizona creating estimated turning point dates clearly marked by the most tragic terrorist attacks to the nation: the shut down in power in NYC in 1965, the World Trade Center Bombing in 1993, and 9/11 2001. Other indexes already constructed include the attacks indexes for the U.S (http://mpra.ub.uni-uenchen.de/1145/01/MPRA_paper_1145.pdf), New York City (http://mpra.ub.uni-muenchen.de/4200/01/MPRA_paper_4200.pdf), and Massachusetts (http://mpra.ub.uni-muenchen.de/4342/01/MPRA_paper_4342.pdf). These indexes must be used as dependent variables in structural models for terrorist attacks, and in models assessing the effects of terrorism over the U.S. economy.A model of cyclical terrorist murder in Colombia; 1950-2004. Forecasts 2005-2019; the econometrics of violence; terrorism; and scenarios for peace in Colombia from 1950 to 2019; scenarios for sustainable peace in Colombia by year 2019; decomposing violence: terrorist murder in the twentieth in the United States; using the Beveridge and Nelson decomposition of economic time series for pointing out the occurrence of terrorist attacks; decomposing violence: terrorist murder and attacks in New York State from 1933 to 2005; terrorist murder; cycles of violence; and terrorist attacks in New York City during the last two centuries; cycles of violence; and terrorist attacks index for the State of Massachusetts